Assesment of Recruitment Process at Specific Company : Case Study from Shipbuilding Industry - Pavlova, Zhanna; Křečková Kroupová, Zuzana, 1972-; Volfová, Jitka, 1982-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2018)
The Bachelor Thesis is focused on the assessment of recruitment process at specific company. When it comes to the aim of the work is to describe recruitment process from the theoretical point of view in the first part of the thesis and also to compare it with the outcomes of the research, which will be described in the second practical part of the work. In the theoretical part, there is explained what is recruitment process, how does it work, its types, methods and main strategies for successful recruitment. Also such processes as selection and induction will be part of the theory in order to provide the full picture of the prosperous recruitment process. Practical part of the thesis is based on the research conducted in specific company in shipbuilding industry, where the outcomes of the interviews are provided, my comments on it as well as comparison between theoretical and practical parts in order to provide better and deeper vision on this process.
Vedoucí práce: Zuzana Křečková Kroupová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses